Long non-coding RNA RP11-284P20.2 promotes cell proliferation and invasion in hepatocellular carcinoma by recruiting EIF3b to induce c-met protein synthesis. Issue 3 (12th March 2020) - Fang, Qin-Liang; Zhou, Jian-Yin; Xiong, Yu; Xie, Cheng-Rong; Wang, Fu-Qiang; Li, Yun-Tong; Yin, Zhen-Yu; Luo, Guo-Hui
Abstract: A newly identified lncRNA designated as RP11-284P20.2 has been identified to be up-regulated in hepatocellular carcinoma (HCC), but its role in HCC remain poorly understood. Quantitative PCR and immunocytochemical analysis were performed using the HCC tissues to identify the potential interaction partners of RP11-284P20.2. Moreover, RP11-284P20.2 was knocked down in HCC cell lines, HepG2 and SMMC7721, to investigate the influence of this lncRNA on cell growth properties. Additionally, RNA fluorescence in situ hybridization and immunofluorescence, RNA immunoprecipitation, and RNA pull-down assays were performed to determine the interaction of RP11-284P20.2 with c-met mRNA and eukaryotic translation initiation factor 3b (EIF3b). Silencing RP11-284P20.2 inhibited cell viability, migration, invasion, and colony formation, and increased apoptosis. Overexpression of c-met abolished these effects of RP11-284P20.2 in HCC cells. Histopathological examination showed that HCC tissues with high RP11-284P20.2 expression had higher c-met protein level than that in HCC tissues with low RP11-284P20.2 expression. However, there was no positive correlation between the expression levels of RP11-284P20.2 and c-met mRNA. RP11-284P20.2 knockdown led to a decease in c-met protein expression level, but did not affect the c-met mRNA expression level. These data suggest that RP11-284P20.2 regulates c-met protein expression level, which is independent of c-Met mRNA expression level. It was also confirmed that RP11-284P20.2 has high affinity toward both c-met mRNA and EIF3b protein, and hence RP11-284P20.2 probably recruits EIF3b protein to c-met mRNA and further facilitates its translation. RP11-284P20.2 promotes cell proliferation and invasion in hepatocellular carcinoma by recruiting EIF3b to induce c-met protein synthesis.